2017
DOI: 10.5539/ijb.v9n3p26
|View full text |Cite
|
Sign up to set email alerts
|

Ants’ Ability in Solving Simple Problems

Abstract: Aiming to know the extent of the ants' cognitive abilities, we set Myrmica ruginodis workers in four problematic situations. We discovered that these ants could walk round a barrier, by foraging and navigating as usual, using known visual cues. They could walk preferentially on smooth substrates instead of rough ones, but did not memorize their choice. This behavior may be due to the easier deposit of pheromones on a smooth substrate. The ants could establish a single way when having only two narrow paths for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In our studies of ants' solving problems (Cammaerts, 2017a), reacting as never before in novel situations (Cammaerts, 2017b), using tools (Cammaerts, 2018), each time the ants succeeded in correctly reacting, they were somewhat rewarded. In the same way, each time the ants did not succeed in correctly responding, they received no reward.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In our studies of ants' solving problems (Cammaerts, 2017a), reacting as never before in novel situations (Cammaerts, 2017b), using tools (Cammaerts, 2018), each time the ants succeeded in correctly reacting, they were somewhat rewarded. In the same way, each time the ants did not succeed in correctly responding, they received no reward.…”
Section: Discussionmentioning
confidence: 90%
“…We have also approached the ontogenesis of Myrmica ants' abilities (M.-C. Cammaerts & R. Cammaerts, 2015a). We also know that these ants can expect the location and the time of food delivery on basis of previous deliveries (M.-C. Cammaerts & R. Cammaerts, 2016a, 2016b, recognize themselves in a mirror (M.-C. Cammaerts & R. Cammaerts, 2015b), individually acquire conditioning and imitate (Cammaerts, 2013), solve simple problems (Cammaerts, 2017a), and can acquire new methods in a novel situation (Cammaerts, 2017b), but cannot use sensu stricto tools (Cammaerts, 2018). The present study was thus a further step in our knowledge of Myrmica ants' biology, bringing information on the ants' ability in learning a sequence of behavior, and on the behavioral process(es) they use to learn such a sequence.…”
Section: Introductionmentioning
confidence: 99%
“…We showed previously that ants are capable of associative learning, memorization, and performing several simple innate behaviors , and that ants can imitate (Cammaerts, 2013a) and learn in the presence of experienced nest mates (Cammaerts & Cammaerts, 2015b). We revealed that the ants can solve simple problems acting according to their behavioral repertory (Cammaerts, 2017a) and can acquire some novel techniques (Cammaerts, 2017b). Here, we showed that the ants were at the limit of using and of learning to use sensu stricto proto-tools and concluded that their cognitive abilities did not include tool use.…”
Section: Discussionmentioning
confidence: 99%
“…The ant brain is highly sophisticated and allows performing multiple and complex acts (Straufeld, 1976). Working with the ant Myrmica ruginodis Nylander 1846, we showed that workers can solve some simple problems: they could walk round a barrier, walk preferentially on smooth substrates instead of rough ones, establish one-way paths when only two narrow paths for going in and out of their nest were available, and push a door to access sugar water (Cammaerts, 2017a). Thereafter, we observed that they could learn novel behaviors, although such behaviors were not initially exhibited: they learned to wet solid sugar or to sweeten pure water to collect sugar water, to open a double door nearly shutting their sugar water tube entrance, and to enlarge a narrow path through a thin cotton barrier plugging their nest entrance (Cammaerts, 2017b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation